Fenomenologi Koperasi Sebagai Katalis Kehidupan Generasi Muda Dalam Upaya Rebranding Koperasi - Purnamawati, Ami; Indriani, Yuanita; Savitri Dewi, Lely (Coopetition : Jurnal Ilmiah Manajemen, 2024)
Transnsforming cooperative values by education institutions in Indonesia would encourage their graduates become the agents of exchange of social and economic lives. Qualitatively cooperative development is still beyond expectation therefore some youths have negative cooperative image. The research purpose was to gain the impacts of cooperative education applying phenomenology method and the informants were alumni of Indonesia Institute of Cooperative Management. The results show that their involvement in cooperative due to its uniqueness, an ideal system, and benefits for members and communities. As a life catalist, cooperative enables people to gain economic benefits, develop thinking paradigm and personality, broader networkings as well. Nevertheless cooperative image is still perceived negatively such as unprosfessional management, single business unit, profit oriented, Syariah contra, and political issues. Some efforts are rebranding cooperative by changing mindset through education and training of cooperative and entrepreneurship, implementing cooperative values and principles, involving youth; hiring professional manager, encouraging members in investment, activating stakeholders; and publishing positive information.